Políticas públicas de salud sexual y reproductiva en el Perú: el ingreso de la reglamentación del aborto terapéutico en la agenda política gubernamental - Leiva Rioja, Zoila (Pontificia Universidad Católica del Perú, 2016)
The objective of the present article is to analyze the process of introducing the regulation of therapeutic abortion into the peruvian governmental agenda, identifying the factors that came together to generate such event, the period of study being between the years 2005 to 2014. The investigation corroborates that said event was possible due to the confluence of certain political and institutional factors on the national stages, the strategy of groups in favor (pro-choice) and against (pro-life) the regulation, and international influence.

El presente artículo tiene como objetivo analizar el proceso de ingreso de la reglamentación del aborto terapéutico en la agenda política gubernamental peruana, así como identificar los factores que confluyeron para generar dicho ingreso, siendo el periodo de estudio entre los años 2005 y 2014. La investigación corrobora que dicho ingreso fue posible gracias a la confluencia de ciertos factores políticos e institucionales del ámbito nacional, de las estrategias de los grupos a favor (pro-elección) y en contra (pro-vida) de la reglamentación, y de la influencia internacional.
Public policies of sexual and reproductive health in Peru: the introduction of therapeutic abortion regulation into the government’s political agenda
Keywords: Therapeutic Abortion; Political Entrepreneurship; Agenda Setting; Public Policy; Pro Choice; Pro Life; Sexual And Reproductive Health; Policy Window; Aborto Terapéutico; Emprendedurismo político; Establecimiento de agenda; Política pública; Pro elección; Pro vida; Salud sexual y reproductiva; Ventana de oportunidad; https://purl.org/pe-repo/ocde/ford#5.06.00